Do E-Money Transactions Affect Consumer Credit Growth, with PayLater as a Moderator? - Randy Hidayat; Abid Djazuli; Ummi Kalsum (International Journal of Applied Business and International Management, 2025)
This study examines the effect of electronic money transactions on consumer credit growth in Indonesian banking, with paylater as a moderating variable. Using monthly secondary data from Bank Indonesia and the Financial Services Authority (OJK), this research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4 to test the proposed hypotheses. The findings reveal that electronic money transactions have a significant negative effect on consumer credit growth, indicating a substitution effect where increased digital payment adoption reduces reliance on bank credit. Conversely, paylater demonstrates a significant positive effect on consumer credit growth, suggesting that buy now pay later services function as a complement to formal banking by creating credit histories that facilitate access to larger bank loans. However, paylater does not significantly moderate the relationship between electronic money transactions and consumer credit growth, implying that the interaction between these two digital financial services is not yet strong enough to alter the direction of influence. These findings contribute to the development of digital financial intermediation theory and offer practical implications for regulators and banking institutions in formulating policies that ensure harmonious development between digital payment ecosystems and formal banking systems